2011
DOI: 10.1007/s10620-011-1871-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Calcineurin Inhibitors on Hepatitis C Recurrence After Liver Transplantation

Abstract: Patients transplanted for hepatitis C virus and treated with cyclosporine versus tacrolimus may have a higher recurrence-free survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…A retrospective study was established in patients who underwent liver transplantation for hepatitis C virus-induced liver disease to evaluate the impact of calcineurin inhibitors, and the cyclosporine group showed improved histological hepatitis C virus recurrence-free survival compared to the tacrolimus group (55.4% vs. 30.8% at 1 year, 18.6% vs. 10.3% at 3 years, 16.7% vs. 8.1% at 5 years, p<0.001) [20]. As for the risk factors associated with survival and histological HCV recurrence, donor age and gender combined with tacrolimus use were taken into account in previous studies [20][23]. Donor age was reported in only four included trials [17], [24][26].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study was established in patients who underwent liver transplantation for hepatitis C virus-induced liver disease to evaluate the impact of calcineurin inhibitors, and the cyclosporine group showed improved histological hepatitis C virus recurrence-free survival compared to the tacrolimus group (55.4% vs. 30.8% at 1 year, 18.6% vs. 10.3% at 3 years, 16.7% vs. 8.1% at 5 years, p<0.001) [20]. As for the risk factors associated with survival and histological HCV recurrence, donor age and gender combined with tacrolimus use were taken into account in previous studies [20][23]. Donor age was reported in only four included trials [17], [24][26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies with small populations have confirmed this in vivo series [26, 120123]. Recently, Spanish groups performing a multicenter retrospective analysis reported that the use of cyclosporine-based immunosuppression regimens and longer treatment duration may protect patients against viral relapse after antiviral treatment [124].…”
Section: Immunosuppression and Recurrent Hepatitis Cmentioning
confidence: 57%
“…Shift of tacrolimus to cyclosporine occurs in patients who experience tacrolimus related side effects. Recently, Kim et al [40] compared recipients of LDLT who received cyclosporine and tacrolimus as immunosuppressive agents. Their results indicated that graft and patient survival rates were similar in the 2 groups, but histologic HCV-recurrence-free survival was significantly higher in the cyclosporine group.…”
Section: Discussionmentioning
confidence: 99%